Compliance of surgical antimicrobial prophylaxis practices in the departments of general surgery and orthopaedics at a tertiary care centre in India - Ravi, Gandham; Chikara, Gaurav; Bandyopadhyay, Arkapal; Handu, Shailendra (International Journal of Advances in Medicine, 2020)
Background: Antimicrobial (AM) prophylaxis is one of the major interventions to prevent surgical site infections. The guideline recommendations are meant for helping the surgeons to select the rationale and effective approach while. This study aimed to assess the compliance of surgical AM prophylaxis in terms of choice of antibiotic, duration and timing of administration using standard international and national guidelines. Methods: A prospective observational study was done in General Surgery and Orthopaedics over a period of one year. All the relevant data was collected and analysed. Results were then compared with standard Clinical Practice Guidelines (CPGAS-2013 and ICMR-2017). Results: In terms of choice of AM, 31.32% of the cases from general surgery and 97.59% of the cases from orthopaedics according to ICMR 2017 guidelines; 28.91% of the cases from general surgery and none of the cases from orthopaedics according to CPGAS 2013 guidelines were found to be compliant. In terms of duration of prophylaxis, 28.91% and 22.89% of the cases from general surgery were found to be compliant to ICMR 2017 and CPGAS 2013 guidelines respectively; but none of the cases from orthopaedics were compliant to either of the guidelines. Timing of administration was found to be compliant with the guidelines in both the departments. Conclusions: Surgical prophylaxis practices were found to be partially compliant with the guidelines in the selected departments.